2014
DOI: 10.1615/critrevtherdrugcarriersyst.2014008193
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Polymeric Electrospun Nanofibers for Drug Delivery

Abstract: Electrospinning is a simple unit operation process by which polymeric nanofibers with diameters ranging from a few nanometers to hundreds of micrometers can be fabricated using an electrostatically operated jet of polymer solution or polymer melt. Nanofibers because of their interesting features, such as surface-to-volume ratio, high surface area, microporosity, and nonwoven structure, provide numerous opportunities to design novel carrier systems for large commodities of therapeutics. Physicochemical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 0 publications
0
29
0
2
Order By: Relevance
“…A special lipid-based oral delivery system archaeosomes, made of the PLFE extracted from S. acidocaldarius, and explore its potential as an oral drug delivery vehicle. Archaeosomes have superior stability in simulated GI fluids, and enable fluorescent labeled peptides to exist in for longer periods in the GI tract after oral administration (Sharma et al, 2014c). Although archaeosomes have slight effect on the transport of insulin across the Caco-2 cell monolayers, the in vivo experiments showed that archaeosomes containing insulin induced lower levels of blood glucose than a conventional liposome formulation.…”
Section: As Carriers For Oral Delivery Of Proteins and Peptidesmentioning
confidence: 99%
“…A special lipid-based oral delivery system archaeosomes, made of the PLFE extracted from S. acidocaldarius, and explore its potential as an oral drug delivery vehicle. Archaeosomes have superior stability in simulated GI fluids, and enable fluorescent labeled peptides to exist in for longer periods in the GI tract after oral administration (Sharma et al, 2014c). Although archaeosomes have slight effect on the transport of insulin across the Caco-2 cell monolayers, the in vivo experiments showed that archaeosomes containing insulin induced lower levels of blood glucose than a conventional liposome formulation.…”
Section: As Carriers For Oral Delivery Of Proteins and Peptidesmentioning
confidence: 99%
“…Yüzey gerilimini düşürmek için çözelti-lere yüzey etken maddeler eklenip daha homojen yapılı lif eldesi sağlanabilmektedir. [4][5][6] Çözeltinin iletkenliği yüksek olursa elektroçekim jeti tarafından daha fazla yük taşınmaktadır. Bu avantajlar, nanoliflerin birçok endüstri alanına rahatlıkla girmesine ve potansiyel kullanım alanı sağlamasına izin vermektedir.…”
Section: Nanoli̇f Yapisini Etki̇leyen Parametrelerunclassified
“…Alignment of polymer backbone structures along fiber axes forms crystal domains [150][151][152], which have provided a foundation for optoelectronics such as nanofiber light sources with color tunability and waveguide capabilities and nanofiber lasers [39,146,148,. Biologically, hybrid nanofiber scaffolds have provided a cell niche conducive to improved attachment, proliferation, and cell differentiation [190][191][192][193][194][195][196][197][198], as well as targeted drug delivery carriers [198][199][200][201][202][203][204][205][206]. Filtration using ONFs [207] equipped with activated carbon has revealed adsorption of volatile organic compounds (VOCs) present in the air [208][209][210], and Scholten et al reported that adsorption and desorption of VOC by electrospun nanofibrous membranes (ENMs) were faster than that of conventional activated carbon [208].…”
Section: Organic Micro-and Nano-fiber Systemsmentioning
confidence: 99%